Communicative Actions of the Online Community Persaudaraan Setia Hati Terate (PSHT) on Instagram - Wiyono, Agus Edi; Muhamad Isnaini; RM Girsang, Lasmery (Lingkar Studi Komunikasi (LISKI), 2025)
In the rapidly evolving digital era, traditional communities such as Persaudaraan Setia Hati Terate (PSHT) have demonstrated remarkable adaptability by strengthening their collective identity through social media platforms like Instagram. This study aims to analyze communication patterns and identity negotiation within the PSHT community on the Instagram account @pshterateindonesia. Using a netnographic approach—an adaptation of ethnography for online research—data were collected through participatory observation of 18,000 posts, comments, and symbols from 2020 to 2024. The findings reveal how community members build solidarity through online interactions, collective narratives, cultural symbols, and communicative practices that reflect traditional PSHT values. The results indicate that the PSHT community successfully strengthens its collective identity in the digital space through educational content, social activities, and the use of distinctive symbols such as black-and-white uniforms and martial arts techniques. Values of brotherhood, discipline, and service to society form the core of the narratives shared on this platform. However, the study also highlights a paradox between the idealism of brotherhood promoted online and incidents of violence involving PSHT members in real life. These findings provide insights into the adaptation of traditional culture to digital spaces, the role of social media in fostering community solidarity, and the challenges of maintaining value consistency across both realms. This research is relevant for understanding online community phenomena in Indonesia and offers recommendations for community managers on leveraging digital platforms to strengthen organizations and promote positive values.Keywords: identity negotiation; communicative action; PSHT community; Instagram social media; Online Solidarity